Nano-sized strontium titanate metal oxide semiconductor oxygen gas sensors - Hu, Ying (2008)
The project focuses on strontium titanate (SrTiO3> material, a very important material for oxygen sensors. The advantages of the material are low cost and stability in thermal and chemical atmospheres. However they have high operating temperatures (> 700 °C) because they are mainly produced by the conventional high temperatures solid-state reaction method and it is very difficult to obtain nano-sized materials.